2017 47th Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN) 2017
DOI: 10.1109/dsn.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

Load-Optimal Local Fast Rerouting for Resilient Networks

Abstract: Abstract-Reliable and highly available computer networks must implement resilient fast rerouting mechanisms: upon a link or node failure, an alternative route is determined quickly, without involving the network control plane. Designing such fast failover mechanisms capable of dealing with multiple concurrent failures however is challenging, as failover rules need to be installed proactively, i.e., ahead of time, without knowledge of the actual failures happening at runtime. Indeed, only little is known today … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…The authors of [18] showed that deterministic failover algorithms are bound to result in a high load even in case of an initially completely connected network which is still highly connected after the failures [18]. The proof has been generalized further by Pignolet et al in [19]. More specifically, the authors showed that: (1) when only relying on destinationbased failover rules, an adversary can always induce a maximum edge load of Ω(ϕ) by cleverly failing ϕ edges; (2) when failover rules can also depend on the source address, an edge load of Ω( √ ϕ) can be achieved, when failing ϕ many edges.…”
Section: B the Deterministic Case Lower Boundmentioning
confidence: 95%
“…The authors of [18] showed that deterministic failover algorithms are bound to result in a high load even in case of an initially completely connected network which is still highly connected after the failures [18]. The proof has been generalized further by Pignolet et al in [19]. More specifically, the authors showed that: (1) when only relying on destinationbased failover rules, an adversary can always induce a maximum edge load of Ω(ϕ) by cleverly failing ϕ edges; (2) when failover rules can also depend on the source address, an edge load of Ω( √ ϕ) can be achieved, when failing ϕ many edges.…”
Section: B the Deterministic Case Lower Boundmentioning
confidence: 95%
“…Detecting port failures falls beyond the scope of this paper as it depends on specific hardware support. FRR mechanisms can generally be categorized along different dimensions, e.g., whether they tolerate only a single link/node failure [52,67,70] or multiple ones [22,62], or whether routing tables are static (e.g., [13,17,45,61,62]) or dynamic (e.g., [25,44]), whether packet header rewriting is required (e.g., [22,42,44,46]) or packet duplication (e.g., [31]), whether provide low stretch [17,23]or load [54,63,68].…”
Section: Related Workmentioning
confidence: 99%
“…Rather, in the packet store-and-forward paradigm, the resiliency is provided by carefully routing the packets around a failed link or network device [3] [4] [5] [6]. However, such an approach requires solving complex combinatorial problems.…”
Section: Introductionmentioning
confidence: 99%